2001
DOI: 10.1575/1912/3476
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Gulf of Maine zooplankton distributions using multiple frequency acoustic, video and environmental data

Abstract: This thesis develops methods useful for estimating zooplankton distributions in the field by combining acoustic models and an integrated set of field data. The accnracy of existing models for fluid-like and elastic-shelled animals is determined by analysis of scattering data from individual aninials in a laboratory tank. Results indicate that simple two-ray scattering rnodels are accurate and allow predictions of size or orientation of an animal to be made for certain animal orientations. A model for gas-beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…This observation of constant pneumatophore volume, combined with the assumption of an ideal gas at constant temperature (T), implies that the density of the gas increases in an amount proportional to the increase in the water pressure (ideal gas law: p pneumatophore V = nRT, which is equivalent to p pneumatophore = ρ pneumatophore RT, where R = universal gas constant = MR, and R is the gas constant for air). Thus, the density contrast between the pneumatophore gas and the surrounding water at depth z was estimated by g = g 0 (1 + 0.1z), where g 0 = 0.0012 is the density contrast between the pneumatophore and the surrounding water at the surface (Warren 2001). Although the pneumatophore is filled with CO, the properties of air were used as an approximation.…”
Section: Appendix a Estimation Of Pneumatophore Target Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation of constant pneumatophore volume, combined with the assumption of an ideal gas at constant temperature (T), implies that the density of the gas increases in an amount proportional to the increase in the water pressure (ideal gas law: p pneumatophore V = nRT, which is equivalent to p pneumatophore = ρ pneumatophore RT, where R = universal gas constant = MR, and R is the gas constant for air). Thus, the density contrast between the pneumatophore gas and the surrounding water at depth z was estimated by g = g 0 (1 + 0.1z), where g 0 = 0.0012 is the density contrast between the pneumatophore and the surrounding water at the surface (Warren 2001). Although the pneumatophore is filled with CO, the properties of air were used as an approximation.…”
Section: Appendix a Estimation Of Pneumatophore Target Strengthmentioning
confidence: 99%
“…With the additional assumption that the sound speed variation of the water is small as a function of depth, it can be concluded that, to first order, the variation in the sound speed contrast, h, with depth is small. Consequently, h was taken to be constant throughout the water column, using a value of 0.22 (again, for air) taken from Warren (2001).…”
Section: Appendix a Estimation Of Pneumatophore Target Strengthmentioning
confidence: 99%
“…The three biggest problems for sonar are that most plankton is small and soft and thus does not e¢ ciently re ‡ect sound, models can only account for general categories of plankton, and the exact sonic properties of the water need to be know to account for changes in the observed signal. The consensus is that sonar may give rough estimates of biomass in certain populations, but is not a suitable tool for determining species or genus, especially for scales less than a millimeter [121], [172], [413], [421].…”
Section: Modern Plankton Measurementsmentioning
confidence: 99%
“…Non-contact methods for in situ measurements revolve around optical and sonic methods. Sonar is unfortunately not able to identify species and has size limits based on the wavelength, so that while it can penetrate further in an aqueous environment, it does not o¤er the detail needed for species-level biological studies [172], [413], [421]. Optical approaches have the best chance at achieving species-speci…c measurements coupled with Tradeo¤ between lateral resolution and depth of …eld.…”
Section: Development: Lab To Oceanmentioning
confidence: 99%
“…There is a clear advantage in using zooplankton sampling methods which return distribution information on the same spatial and temporal scale as physical measurements. Multifrequency acoustic methods are a promising, and increasingly popular, approach to estimate zooplankton distribution and biomass patterns [ Greenlaw , 1979; Holliday and Pieper , 1980; Wiebe et al , 1996; Holliday et al , 1998; Warren , 2001; Holliday et al , 2003]. These instruments provide scientists with the ability to rapidly map distributions of scatterers at high spatial resolution without disturbing the observed organisms.…”
Section: Introductionmentioning
confidence: 99%